P78 MedEd Collaborative: a new research collaborative to promote medical education research. (8th April 2021) - ,; Byrne, Matthew H V; Ashcroft, James; Alexander, Laith; Wan, Jonathan C M; Harvey, Anna; Schindler, Nick; Brown, Megan E L; Burford, Bryan; Vance, Gill; Byrne, Matthew
Abstract: Introduction: In response to the disruption to medical education caused by COVID-19, there is a need for wide-scale robust medical education research and the generation of research capacity for the future. Trainee research collaboratives have demonstrated they can nurture the research skills of students and trainees while delivering high quality research outputs. However, we have been unable to identify a permanent medical education research collaborative for trainees and students. Methods: We started the MedEd Collaborative in September 2020 to fill this gap, consisting of a trainee- and student-led medical education research collaborative supported by senior medical education experts and clinicians. Results: Our vision is to increase engagement of students and trainees in high-quality medical education research that informs practice. The MedEd Collaborative will engage students and trainees in medical education research by completing at least one national multicentre study per year, the first being the COVID Ready 2 study. This is a national cross-sectional survey of the educational impact of medical student volunteering during the COVID-19 pandemic. Conclusions: We anticipate the MedEd collaborative will: increase exposure to medical education research, thereby increasing the number of medical students and trainees aiming to pursue an academic medical education career; provide training in medical education research methodologies, such as qualitative analysis; improve the quality of medical education research outputs from students and trainees; encourage collaboration between medical schools and deaneries; and provide support to other trainee research collaboratives that aim to explore education research in their own specialties.